Case Study : Faizal Motor Work / Amirah Fatini Berahim @ Ab Rahman - Berahim @ Ab Rahman, Amirah Fatini (2020)
Faizal Motor Works is a workshop that successfully solved the problems of many types of vehicles especially luxury and high-performance vehicles such as Mercedes, BMW, Range Rover, and Bentley. It has been operating since 2010 in front of Mr. Faizal’s house and start has a workshop at Lundang approximately 4 years. Faizal Motor Works offered all services related to the car except for body and paint, and alignment. The main problem that faced by Faizal Motor Works is lack of manpower and small workshop. The company should find more experienced workers in order to increase the sales while maintaining quality of service. The new workers should be well trained. Other than that, the company also need to find wider workshop to receive more cars in a day or add more branches